Design of a two-photon fluorescent probe for ratiometric imaging of endogenous hypochlorite in mitochondria. (October 2020) - Li, Linke; Wang, Xinru; Sun, Chuan; Xu, Tingting; Yang, Zhijian; Zhang, Zhengsong; Feng, Yan; Fang, Min; Chen, Man; Wang, Xin; Meng, Xiangming
Abstract: Hypochlorite (ClO − ) is associated with complex physiological activities in the living system. Therefore, it is necessary to develop a tool for visualizing ClO − at the cellular and subcellular levels. We herein presented a two-photon fluorescent probe MCL with dual response sites and ratiometric response to ClO − . The response sites of two oxathiolane rings endowed probe MCL with superior selectivity for ClO − over other analytes. The fast response and high sensitivity of MCL to ClO − were also well demonstrated. In addition, probe MCL was confirmed to possess accurate mitochondrial targeting ability through a co-localization study. The good two-photon sensing performance of MCL for exogenous and LPS-induced endogenous ClO − in living cells was validated by dual-color imaging. Moreover, we employed the probe to successfully monitor endogenous ClO − in H2 S-stimulated cells by dual-channel mode for the first time. Graphical abstract: A two-photon fluorescent probe with dual response sites for ratiometric imaging of mitochondrial hypochlorite in living cells has been developed. Image 1 Highlights: A ratiometric two-photon fluorescent probe was designed for monitoring ClO − . The probe showed ultrafast response and high selectivity for ClO − detection. Dual-channel imaging of exogenous and endogenous ClO − in mitochondria was obtained. The probe was used for dual-color imaging of H2 S-induced ClO − in cells for the first time .